Use of Digital Social Media at Night, Awareness of the Associated Risks, Beliefs and Driving Factors - Adeoye, Adeponle Olayode; Jegede, Ayodele Samuel (Italian Sociological Review, 2023)
Studies have reported the effects of using digital social media (DSM) platforms at night on sleep and health. However, there is a paucity of studies on awareness of the risks and determinants of this behaviour. This study examined awareness about the risks associated with the nocturnal use of DSM and the factors driving its use at night. Twenty in-depth interviews were conducted in Ibadan North Local Government Area of Oyo State to assess awareness of DSM users about the risks associated with nocturnal use of DSM, beliefs about nocturnal use of DSM, activities driving the use of the platform at night and quality of sleep of DSM users. Data analysis involved verbatim transcription, content analysis, and thematic organization of responses. Users are aware of the risks associated with the nocturnal use of DSM, but there is a lack of willingness to take them seriously among some users. Participants believe that the use of DSM at night is a form of leisure. Networking, social obligations, engagements in the daytime, and free and affordable internet data were the identified factors driving the nocturnal use of DSM. The study concluded that users are aware of the risks associated with the nocturnal use of DSM, but the willingness to take them seriously differs among them. Social activities are the drivers of the nocturnal use of DSM, predisposing users to poor sleep and its effects. These findings suggest the need for more sensitization about the benefits of adequate sleep at night on health to reduce risky behaviours that may affect sleep such as the nocturnal use of DSM.